Persistent Genital Arousal Disorder: Two Case Studies and Exploration of a Novel Treatment Modality - Meghan Scantlebury; Romeo Lucas (Mary Ann Liebert, 2023)
Persistent genital arousal disorder (PGAD) is characterized by persistent unwanted feelings of sexual arousal that can be debilitating. Despite first being defined >20 years ago, the precise etiology and treatment of this disorder remain elusive. Mechanical disruption of nerves, neurotransmitter changes, and cyst formation have all been considered as etiologies involved with the development of PGAD. With limited and ineffective treatment modalities, many women live with their symptoms untreated or undertreated. To broaden the literature, we present two cases of PGAD and present a novel treatment modality of the disorder with the use of a pessary. Although there was subjective success in dampening the symptoms, they were not completely resolved. These findings open the door for the potential of similar treatments in the future.